Probability‐based design of spun concrete beam‐columns - Kudzys, Antanas; Kliukas, Romualdas (Journal of Civil Engineering and Management, 2010)
The attention of engineers is turned to the application of precast spun concrete columns reinforced by high‐strength steel bars for office and administrative buildings. The paper discusses a possibility of using the reliability index approach to designing beam‐columns of building frames and analyses resistance criteria for beam‐columns of annular cross sections as compression members with bending moments and bending members with compressive forces. First and second order effects of beam‐columns are considered. The article also presents time‐dependent resistance safety margin and its stationary equivalent and investigates the unsophisticated applied models for probability‐based design of frame beam‐columns. The design of a beam‐column of the braced frames is illustrated providing a numerical example.First Published Online: 10 Feb 2011